1981
DOI: 10.1523/jneurosci.01-07-00710.1981
|View full text |Cite
|
Sign up to set email alerts
|

Invariant characteristics of a pointing movement in man

Abstract: Simple arm movements involving forward projection of the hand toward a target were studied by measuring simultaneous wrist position in three-dimensional space and changes in elbow angle. An attempt was made to identify those features of the movement which exhibit invariant characteristics under the hypothesis that such invariances may reflect the operations by which central processes participate in the organization of the movement. The first such invariance to be identified was that the trajectory in space is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
238
3

Year Published

1987
1987
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 589 publications
(254 citation statements)
references
References 29 publications
13
238
3
Order By: Relevance
“…Finding unambiguous solutions for this transformation is not a trivial task. The CNS overcomes this problem routinely and often generates reproducible behavior that exhibits invariant parameters, which have been observed in classical studies such as Soechting and Lacquaniti (1981), Atkeson and Hollerbach (1985), Morasso (1981), and Flash and Hogan (1985). The results of these studies imply additional constraints that are realized within the nervous system and have led to the formulation of a range of hypotheses concerning the generation of goal-directed limb movements.…”
Section: Introductionmentioning
confidence: 88%
“…Finding unambiguous solutions for this transformation is not a trivial task. The CNS overcomes this problem routinely and often generates reproducible behavior that exhibits invariant parameters, which have been observed in classical studies such as Soechting and Lacquaniti (1981), Atkeson and Hollerbach (1985), Morasso (1981), and Flash and Hogan (1985). The results of these studies imply additional constraints that are realized within the nervous system and have led to the formulation of a range of hypotheses concerning the generation of goal-directed limb movements.…”
Section: Introductionmentioning
confidence: 88%
“…In modern movement science, the debate about extrinsic vs. intrinsic motor goals began with studies which found that some key properties of the movement trajectories of the end-effector were invariant in the outer Cartesian space, across repetitions, conditions, and subjects: movement paths of the endeffector are gently curved and their tangential velocity profiles are bell-shaped with a single peak (Morasso, 1981;Abend et al, 1982). Soechting and Lacquaniti (1981), studied pointing arm movements in a vertical plane and interpreted extrinsic invariants as the consequence of the temporal coordination of the joint angles at the shoulder and the elbow (see Flanagan and Ostry (1990) for a similar conclusion for jaw movements). Uno et al (1989) and Kawato et al (1990) argued that optimization principles may add intrinsic to extrinsic constraints.…”
Section: Extrinsic Versus Intrinsic Motor Goals In Limb Movementsmentioning
confidence: 99%
“…At the time the minimum-jerk theory was proposed, it concisely summarized the majority of the available arm movement data: Morasso (1981) and Flash and Hogan (1985) had found straight hand paths for various horizontal-plane movements, Hollerbach and Flash (1982) and Soechting and Lacquaniti (1981) had reported data suggesting that trajectory shape is unaffected by changes in movement duration, and the studies of Abend et al (1982), Georgopoulos, Kalaska, and Massey (1981), and Morasso (1981) had shown that velocity profiles are bellshaped and approximately symmetric. Because of its excellent agreement with these experimental observations, the minimum-jerk principle became one of the most influential motor control theories.…”
Section: Cartesian-space Planningmentioning
confidence: 99%